2000
DOI: 10.4049/jimmunol.164.8.4340
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Complement in Antibody-Mediated Inflammation: C5-Deficient DBA/1 Mice Are Resistant to Collagen-Induced Arthritis

Abstract: Collagen-induced arthritis (CIA) represents an animal model of autoimmune polyarthritis with significant similarities to human rheumatoid arthritis that can be induced upon immunization with native type II collagen. As in rheumatoid arthritis, both cellular and humoral immune mechanisms contribute to disease pathogenesis. Genotypic studies have identified at least six genetic loci contributing to arthritis susceptibility, including the class II MHC. We have examined the mechanism of Ab-mediated inflammation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(54 citation statements)
references
References 52 publications
3
50
0
Order By: Relevance
“…Likewise, studies have also shown that perpetuation of inflammation coincides with increased levels of the anaphylatoxin C5a in the synovial fluid of RA patients [9]. Further studies in mice identifying C5 as a candidate gene and showing that C5 deficiency results in lower incidence and less-severe disease course support the role of this gene in inflammation [7,11]. It is therefore likely that although the primary function of the complement system is to protect the host from microorganisms, a deregulated activity of its central component, C5, can play a substantial role in inflammatory diseases as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, studies have also shown that perpetuation of inflammation coincides with increased levels of the anaphylatoxin C5a in the synovial fluid of RA patients [9]. Further studies in mice identifying C5 as a candidate gene and showing that C5 deficiency results in lower incidence and less-severe disease course support the role of this gene in inflammation [7,11]. It is therefore likely that although the primary function of the complement system is to protect the host from microorganisms, a deregulated activity of its central component, C5, can play a substantial role in inflammatory diseases as well.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in several experimental animal models for RA, innate immune responses mediated by a diversity of players have been implicated in arthritis. In this respect, a prominent role for the complement system has been identified as mice deficient in complement factors are resistant to arthritis, and as it has been shown that targeting complement component 5 (C5) by antibodies prevents the onset of arthritis and reduces the clinical severity in mouse models for arthritis [7,8]. Likewise, the observation that high levels of C5a , a potent chemoattractant, are found in synovial fluid of RA patients combined with the fact that C5a receptor -deficient mice are also resistant to arthritis induction, indicate a central role for these mediators in arthritis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibodies prevalent in RA might play an important role in the disease development and most widely used animal models are dependent on antibody-mediated pathologies [14][17]. Antibodies in the form of immune complexes might play a central role in triggering inflammatory pathways in the joint [18], especially C5a binding to these immune complexes can attract granulocytes to the articular cartilage that can release inflammatory mediators (proteases, cytokines, chemokines, and reactive oxygen and nitrogen radicals) perpetuating inflammation and autoimmunity. In the present study, breaking tolerance towards C5a by vaccination to induce polyclonal anti-C5a response, C5a/C5b neutralizing capacity of the induced antibodies and their effect on arthritis development in various mouse models were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, complement activation is associated with the chronic inflammation in rheumatoid arthritis and osteoarthritis (33). Recent studies in mice deficient in various complement factors have shown that both the classical and alternative pathways are important in the development of collageninduced arthritis (34,35). It has been proposed that inhibition of C5a generation may be a successful therapeutic approach for treatment of rheumatoid arthritis (36).…”
Section: Discussionmentioning
confidence: 99%